Analysis of work posture, workload and work stress against nurse burnout syndrome - Rizki Racheshi, Ari; Syafriadi , Mei; Caesarina Novi Marchianti , Ancah (Science Midwifery, 2024)
This study aims to examine work posture, workload and work stress on burnout syndrome symptoms experienced by nurses when handling patients with COVID-19, an analytical observational research with a survey study design was used in this study. The sample of this study were 54 nurses in the Special Isolation Room for COVID-19 patients at RSUD Dr. Soetomo Surabaya and RSUD dr. Soebandi Jember, determining the sample using purposive sampling technique. Data were collected using observation sheets and questionnaires. Data were analysed by bivariate test and multivariate test with multiple linear regression analysis and ordinal regression. The results showed that the work posture of nurses handling COVID-19 patients was in the low to moderate risk category and workload, work stress and symptoms of burnout syndrome in nurses handling COVID-19 patients at moderate to high levels. Work posture and workload variables do not have a significant effect on symptoms burnout syndrome (p < 0.05) while work stress has a significant effect on symptoms burnout syndrome (p < 0.05). The health care system needs to pay attention to the safety and health of nurses by creating a safe and comfortable atmosphere, forming work teams, organizing work and fulfilling the availability of PPE and prioritising mental health aspects by providing psychological counselling for nurses in charge of handling COVID-19 patients.